2021
DOI: 10.1101/2021.04.06.21254961
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“It’s possibly made us feel a little more alienated”: How people from ethnic minority communities conceptualise COVID-19 and its influence on engagement with testing

Abstract: Objectives:The cultural beliefs, practices and experiences of ethnic minority groups, alongside structural inequalities and the political economy play a critical, but overlooked role in health promotion. The current study aims to address this deficit, understanding how these groups conceptualise COVID–19, and how this influences engagement in testing, with the future aim of developing targeted communications to address the challenges of testing uptake. Method:Black (African and Caribbean) and South (Asian Indi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

6
0

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
(36 reference statements)
0
12
1
Order By: Relevance
“…Robust interventions relying on behavioural science to tackle misinformation using social media and evaluations are a plausible next step to address immunisation challenges for COVID-19 vaccines but also routine vaccines. Building trust in public health messaging, identifying information gaps, finding innovate ways of disseminating health information, and detecting and responding to misinformation as it emerges remain a priority for public health 66 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Robust interventions relying on behavioural science to tackle misinformation using social media and evaluations are a plausible next step to address immunisation challenges for COVID-19 vaccines but also routine vaccines. Building trust in public health messaging, identifying information gaps, finding innovate ways of disseminating health information, and detecting and responding to misinformation as it emerges remain a priority for public health 66 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from both testing and vaccination suggests that increased inequalities would be a possible harm of health certification. Participation in NHS Test & Trace is lower in marginalised groups [71,72] and in areas of high deprivation [73]. The Liverpool mass testing pilot found that uptake in the most deprived areas (16.8%) was half that in the least deprived areas (33.4%) [74].…”
Section: Maximising Benefits and Minimising Harmsmentioning
confidence: 99%
“…Data from the UK and other countries suggest that those with lower incomes or education and from minority ethnic groups have lower intentions to undergo COVID-19 vaccination than others [75][76][77]. In part these differences in testing and vaccination uptake reflect higher mistrust in government amongst marginalised communities [71,[78][79][80]. Stigmatisation, discrimination and racism might also reduce migrants' and ethnic minority communities' willingness to come forward [71].…”
Section: Maximising Benefits and Minimising Harmsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, we aim to develop a theory explaining the relationship between the development of conspiratorial beliefs around COVID-19 and such behaviours. Understanding this relationship and the development and nature of conspiracy beliefs is important for practitioners who are striving to communicate and create interventions to promote COVID health protective behaviours; such as vaccination up-take and testing, which has been lower in Britain’s Black community compared to other minority ethnic groups (Office for National Statistics, 2021; Vandrevala et al, 2022).…”
Section: Introductionmentioning
confidence: 99%